Theoretical methods of teaching creative thinking in mathematics under the competencies approach: Cooperative Education and Problem Solving as a Model - Boutheldja, Ahmed; Benziane, malika (Journal of Human Sciences, 2021)
Thinking is one of the most important tributaries of man to adapt to an environment and ensure its survival and continuity of its strict type means developing its skills through educational programs and curricula related to the approach to competencies approach. Algeria attached importance in the context of successive educational reform approaches from the year 2002 through educational programs that aim to develop thinking and thinking skills and the learner in order to reach what is effective in school data in a curriculum to exceed its investment in the school environment to a life of adaptation. Through this article, we seek to investigate the theoretical mechanisms of creative thinking in teaching mathematics, where we address each of the methods of cooperative learning and problem solving in building educational positions that stimulate the learner within the dynamics of the group of comrades, which may lead to achieving the desired goals